Novel glyconanoconjugates: synthesis, characterization and bioapplications. Issue 107 (7th November 2016) - Telli, Fatma Cetin; Demir, Bilal; Barlas, Fırat Barıs; Guler, Emine; Timur, Suna; Salman, Yesim
Abstract : The impressive properties of nanoparticles (NPs) have caused them to gain considerable attention for biological applications such as cancer therapy. Abstract : The impressive properties of nanoparticles (NPs) have caused them to gain considerable attention for biological applications such as cancer therapy. Among the many nanoparticles used in the treatment of cancer, carbohydrate derivatized modified NPs lead the way with enhanced internalization and therapy efficacy for cancerous cell lines. In this research, an aminochlorase Schiff base, which can be beneficial as a therapy material, with a galactose residue was used as a potentially active modifier. Gold and silver nanoparticles (AuNPs and AgNPs) can be readily modified with a sugar Schiff base ligand (1 ) by using cysteamine hydrochloride residues as a linker between the nanoparticle surface and the ligand. The resulting glyco-nanoparticles were characterized using transmission electron microscopy, X-ray photoelectron microscopy and spectrophotometric techniques. Additionally, this modification type within a galactose derived Schiff base is the first work with a bioapplication, especially in radiotherapy. For further biological applications in cancerous cell lines, two commonly used cell lines, human cervix adenocarcinoma (HeLa) and human lung carcinoma cell line (A549) were introduced into the biological evaluation of those NP–ligand conjugates and satisfactory radioactivity results were obtained because of the radiosensitizing effect of the AuNPs and AgNPs.